Negative plate, preparation method thereof and lithium ion battery
By introducing a polymer layer that can be dissolved in the electrolyte solution into the negative electrode sheet of the lithium-ion battery to form a groove, the problem that the negative electrode sheet in the prior art cannot guarantee the safety of the battery is solved, and higher ionic conductivity and maximum magnification are achieved Charging performance, while avoiding safety risks caused by negative electrode powder residue.
Patent Information
- Application Number
- CN202411327244.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-03
AI Technical Summary
The existing lithium-ion battery negative electrode sheet cannot guarantee the safety of the battery while obtaining grooves. Laser etching causes residual negative electrode powder to cause self-discharge and safety risks.
Using a negative electrode sheet of the current collector, including the first negative electrode active layer and the second negative electrode active layer, the groove is formed by dissolving the polymer boss in the electrolyte to form an additional ion transmission channel, thereby improving the maximum charging performance of the lithium battery, and The migration path of the active ions is shortened by dissolution of the polymer layer, and the negative electrode powder residue is avoided.
It improves the ionic conductivity and high-speed charging performance of lithium batteries, enhances the safety of the battery, and avoids self-discharge and safety risks caused by the residue of negative electrode powder.
Smart Images

Figure CN119252868A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Currently, commercial graphite negative electrode materials have problems such as poor transmission kinetics under fast charging conditions, the generation of "dead lithium" due to the lithium-repellent properties of the surface, and high ion transmission resistance caused by thick graphite electrodes. To address the above problems, the industry currently mainly uses laser etching of grooves with uniform spacing on the surface of the negative electrode sheet to meet the needs of high-rate charging of lithium batteries by constructing additional ion transmission channels and widening the spacing between graphite layers.
[0003] However, this method brings an obvious problem. The negative electrode powder etched by laser cannot be effectively removed, causing slight self-discharge inside the battery, which is not conducive to long-term storage of the battery. If the self-discharge is too fast, it may even cause the battery to bulge, posing a safety risk.
[0004] Therefore, the existing negative electrode sheet cannot obtain the groove while ensuring the safety of the battery. Summary of the invention
[0005] The main purpose of the present invention is to provide a negative electrode sheet and a preparation method thereof, and a lithium ion battery, aiming to solve the problem that the existing negative electrode sheet of a lithium ion battery cannot obtain a groove while ensuring the safety of the battery.
[0006] To achieve the above object, the present invention provides a negative electrode sheet, which includes:
[0007] current collector;
[0008] A first negative electrode active layer, wherein the first negative electrode active layer is disposed on at least one surface of the current collector;
[0009] A polymer layer, the polymer layer comprising a plurality of polymer bosses, the plurality of polymer bosses being arranged at intervals on a surface of the first negative electrode active layer facing away from the current collector, wherein the polymer bosses are made of a polymer that can be dissolved in an electrolyte;
[0010] A second negative electrode active layer, the second negative electrode active layer comprising a plurality of negative electrode active bosses, the plurality of negative electrode active bosses being arranged at intervals on a surface of the first negative electrode active layer facing away from the current collector, and each of the negative electrode active bosses being arranged between two adjacent polymer bosses;
[0011] Wherein, the polymer boss is used to dissolve in the electrolyte when the negative electrode sheet is placed in the electrolyte, so as to form a groove between two adjacent negative electrode active bosses.
[0012] Preferably, the polymer is selected from at least one of waterborne polyurethane, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, and polyvinylidene fluoride;
[0013] and / or, the molecular weight of the polymer is 3000 to 50000;
[0014] And / or, the melting point of the polymer is 50°C to 80°C.
[0015] Preferably, the distance between any two adjacent polymer bosses is the same;
[0016] And / or, the cross-sectional area of each polymer boss is greater than or equal to 0.01 mm 2 And less than 0.1mm 2 .
[0017] Preferably, the distance between two adjacent polymer bosses is greater than or equal to 0.5 mm and less than 3 mm.
[0018] Preferably, the cross-sectional area of a single groove and the molecular weight of the polymer satisfy the relationship: 4≤S / M*10 7 ≤67;
[0019] Wherein, S is the cross-sectional area of a single groove, and M is the molecular weight of the polymer.
[0020] Preferably, the first negative electrode active layer includes a first active material, the second negative electrode active layer includes a second negative electrode active material, and the first active material and the second active material are each independently at least one of graphite, hard carbon, soft carbon, silicon-based material, titanium-based material, nitride, tinide, metallic lithium, silicon-doped graphite, and lithium titanate.
[0021] Preferably, the thickness of the polymer layer is less than or equal to the thickness of the first negative electrode active layer;
[0022] And / or, the thickness of the polymer layer is the same as the thickness of the second negative electrode active layer.
[0023] The present invention further provides a method for preparing the negative electrode sheet as described above, the method comprising:
[0024] Coating a first negative electrode slurry on at least one surface of the current collector to obtain a first negative electrode active layer;
[0025] Coating a second negative electrode slurry and a polymer slurry on the surface of the first negative electrode active layer facing away from the current collector to form a composite layer to obtain the negative electrode sheet;
[0026] In the composite layer, the negative electrode slurry and the polymer slurry are both obtained by multi-striped coating.
[0027] Preferably, the step of coating the second negative electrode slurry and the polymer slurry on the surface of the first negative electrode active layer facing away from the current collector to form a composite layer comprises:
[0028] Coating the polymer slurry on the surface of the first negative electrode active layer facing away from the current collector in a multi-striped coating manner and performing a second drying process to form a polymer layer;
[0029] Applying a second negative electrode slurry in the gaps of the pre-coat layer to fill the gaps and performing a third drying process to obtain the composite layer;
[0030] or,
[0031] Coating a second negative electrode slurry on the surface of the first negative electrode active layer facing away from the current collector by a multi-striped coating method and performing a third drying process to obtain a second negative electrode active layer;
[0032] Applying the polymer slurry to fill the gaps in the second negative electrode active layer and performing a second drying process to obtain the composite layer;
[0033] or,
[0034] The polymer slurry and the second negative electrode slurry are simultaneously subjected to multi-stripe coating by using a double die head and then subjected to a fourth drying process to obtain the composite layer.
[0035] Preferably, after coating the first negative electrode slurry on at least one surface of the current collector and before obtaining the first negative electrode active layer, the preparation method further comprises: performing a first drying treatment on the current collector coated with the negative electrode slurry.
[0036] Preferably, the first drying process is selected from one of a first baking process and an ultraviolet light curing process;
[0037] And / or, the second drying process, the third drying process and the fourth drying process are independently selected from one of a second baking process and an ultraviolet light curing process.
[0038] Preferably, the temperature of the first drying treatment is 40°C to 50°C;
[0039] And / or, the temperature of the second drying treatment is 55°C to 65°C;
[0040] And / or, the conditions of the UV curing treatment include: UV light intensity of 900W / cm 2 ~1100mW / cm 2 , the curing processing power is 30% to 50%, and the curing processing time is 5s to 15s.
[0041] Preferably, the first negative electrode slurry comprises a first negative electrode active material, a binder, a thickener, and a first solvent;
[0042] and / or, the polymer slurry comprises a polymer and a second solvent;
[0043] And / or, the second negative electrode slurry includes a second negative electrode active material, a binder, a thickener, and a first solvent.
[0044] Preferably, the concentration of the polymer slurry is greater than or equal to 10 mg / mL and less than or equal to 50 mg / mL;
[0045] And / or, the second solvent is deionized water.
[0046] Preferably, the first negative electrode active material and the second negative electrode active material are each independently at least one of graphite, hard carbon, soft carbon, silicon-based material, titanium-based material, nitride, tin compound, metallic lithium, silicon-doped graphite, and lithium titanate; the binder is selected from at least one of polyvinylidene fluoride, carboxymethyl cellulose, polyvinyl alcohol, and sodium alginate; the thickener is selected from at least one of sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, and guar gum; the first solvent is selected from at least one of deionized water, N-methylpyrrolidone, dimethylformamide, and dimethylacetamide;
[0047] and / or, the mass ratio of the first negative electrode active material, the binder and the thickener is (96-98): (1-2): (1-2);
[0048] And / or, the mass ratio of the second negative electrode active material, the binder and the thickener is (96-98):(1-2):(1-2).
[0049] The present invention further provides a lithium-ion battery, which includes a shell, and a battery cell and an electrolyte disposed in the shell; the battery cell includes a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet;
[0050] Wherein, the negative electrode sheet is the negative electrode sheet as described above or the negative electrode sheet prepared by the method as described above.
[0051] The beneficial effect of the technical solution of the present invention is that: the present invention introduces a polymer layer into the negative electrode sheet, and utilizes its ability to be soluble in the electrolyte, so that grooves can be formed by physical dissolution of the polymer by the electrolyte, thereby achieving the purpose of constructing additional ion transmission channels and widening the spacing between the anode sheets, thereby improving the high-rate charging performance of the lithium battery, and because the polymer layer dissolves in the electrolyte, the migration path of active ions in the negative electrode can be shortened, thereby improving the ionic conductivity. Compared with the existing negative electrode sheets, the negative electrode sheet of the present invention will not produce residual negative electrode powder, which can improve the safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 Schematic diagram of the negative electrode structure of an embodiment of the present invention.
[0053] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0054] The scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, top, bottom, side...) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0056] It should also be noted that when an element is referred to as being "fixed on" or "disposed on" another element, it may be directly on the other element or there may be an intermediate element at the same time. When an element is referred to as being "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time.
[0057] In addition, the descriptions involving "first", "second", etc. in the embodiments of the present invention are only for descriptive purposes and cannot be understood as indicating or suggesting their relative importance or implicitly indicating the number of the indicated technical features.
[0058] For technical defects in related technologies, see Figure 1 The present invention provides a negative electrode sheet, which includes:
[0059] Current collector 10;
[0060] A first negative electrode active layer 20, wherein the first negative electrode active layer 20 is disposed on at least one surface of the current collector 10;
[0061] A polymer layer 30, wherein the polymer layer 30 comprises a plurality of polymer bosses, wherein the plurality of polymer bosses are arranged at intervals on a surface of the first negative electrode active layer 20 facing away from the current collector 10, wherein the polymer bosses are made of a polymer that can be dissolved in an electrolyte;
[0062] A second negative electrode active layer 40, wherein the second negative electrode active layer 40 comprises a plurality of negative electrode active bosses, wherein the plurality of negative electrode active bosses are arranged at intervals on the surface of the first negative electrode active layer 20 facing away from the current collector 10, and each of the negative electrode active bosses is arranged between two adjacent polymer bosses;
[0063] Wherein, the polymer boss is used to dissolve in the electrolyte when the negative electrode sheet is placed in the electrolyte, so as to form a groove between two adjacent negative electrode active bosses.
[0064] Specifically, the present invention introduces a polymer layer into the negative electrode sheet, and utilizes its property of being soluble in the electrolyte to form grooves through the physical dissolution of the polymer by the electrolyte, thereby achieving the purpose of constructing additional ion transmission channels and widening the spacing between the anode sheets, thereby improving the high-rate charging performance of the lithium battery. In addition, since the polymer layer dissolves in the electrolyte, the migration path of active ions (lithium ions in lithium-ion batteries) in the negative electrode can be shortened, thereby improving the ionic conductivity. Compared with the existing negative electrode sheets, the negative electrode sheet of the present invention will not produce residual negative electrode powder, which can improve the safety of the battery.
[0065] In some embodiments, the polymer is selected from at least one of waterborne polyurethane (PU), polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PAMA), and polyvinylidene fluoride (PVDF); and / or the molecular weight of the polymer is 3000 to 50000; and / or the melting point of the polymer is 50°C to 80°C.
[0066] In this embodiment, the above-mentioned polymers can all be well dissolved in the electrolyte to form grooves, thereby constructing additional ion channels, widening the spacing between the anode sheets, shortening the migration path of the active ions in the negative electrode, and thus improving the ionic conductivity and high-rate current charge and discharge performance of the battery; the molecular weight and melting point of the polymer will affect the subsequent electrolyte dissolution of the polymer to form grooves, and the molecular weight and melting point within the above-mentioned range can facilitate the dissolution of the polymer to form grooves.
[0067] In some embodiments, the polymer is preferably waterborne polyurethane with a molecular weight of about 10,000.
[0068] Waterborne polyurethane has a typical two-phase structure. The molecular soft segment composed of polyether can undergo solvation reaction with the salt in the electrolyte, promote ion transport, and improve the electrolyte ion conductivity, thereby improving the cycle performance of the battery; the molecular hard segment formed by polar groups such as carbamate can produce physical cross-linking points and has good SEI (solid electrolyte interface) film-forming properties, providing a guarantee for improving the capacity attenuation over long cycles.
[0069] Specifically, lithium battery electrolytes are usually composed of organic solvents, such as ethylene carbonate, propylene carbonate, diethyl carbonate, etc. These organic solvents have a certain polarity. The molecular structure of polyurethane contains ester groups, ether bonds, carbamate bonds, etc. These polar groups give it a certain polarity. According to the principle of similar compatibility, the polar part of polyurethane interacts with the polarity of the organic solvent in the electrolyte, resulting in the polyurethane being able to dissolve in the electrolyte.
[0070] In this embodiment, the electrolyte may include ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) as solvents. The selection of this component can ensure that the battery has a higher energy density and cycle life, and has better solubility for the polymer.
[0071] In some embodiments, the spacing between any two adjacent polymer bosses is the same; and / or the cross-sectional area of each polymer boss is greater than or equal to 0.01 mm 2 And less than 0.1mm 2 .
[0072] Specifically, when the width of each polymer boss is too narrow, it will pose certain challenges to the polymer coating process and will result in insufficient ion channels, which will lead to decreased cycle performance; when it is too wide, it will easily cause two adjacent polymer bosses to overlap, resulting in decreased cycle performance, and the width of the polymer boss is too wide, which will also lead to fewer negative electrode active bosses, which will easily lead to problems such as reduced battery capacity, shortened cycle life, increased internal resistance, unstable electrochemical performance, and reduced energy density. If the spacing between two adjacent polymer bosses is unequal, it will affect the overall performance of the prepared battery cell. When the width of the pole piece remains unchanged and the coating width is the same, the spacing is equal, and more grooves can be accommodated. Unequal spacing will result in a reduction in the number of grooves.
[0073] In some embodiments, the distance between two adjacent polymer bosses is greater than or equal to 0.5 mm and less than 3 mm.
[0074] In this embodiment, when the spacing between two adjacent polymer bosses is too narrow, it will pose certain challenges to the polymer coating process, which may easily cause the two adjacent polymer bosses to overlap, thereby causing performance degradation; when the spacing between two adjacent polymer bosses is too wide, the constructed ion channel is insufficient, which will also cause a decrease in cycle performance; preferably, the spacing between two adjacent polymer bosses is 1.0mm to 3.0mm.
[0075] In some embodiments, the cross-sectional area of a single groove and the molecular weight of the polymer satisfy the relationship: 4≤S / M*10 7 ≤67;
[0076] Wherein, S is the cross-sectional area of a single groove, and M is the molecular weight of the polymer.
[0077] For example, when the cross-sectional area of the groove is 1 mm*18 μm and the molecular weight is 10,000, S / M*10 7 =18, and its dissolution effect in the electrolyte is the best. When the molecular weight of the polyurethane used increases, its dissolution effect in the battery cell will become worse, which will cause residual blockage of the polymer in the groove, occupying the volume of the groove, thereby affecting the consistency of liquid retention. When the molecular weight of the polymer decreases, the interaction between PU and the electrolyte is weakened, affecting the lithium ion ion conductivity.
[0078] In some embodiments, the first negative electrode active layer includes a first negative electrode active material, the second negative electrode active layer includes a second negative electrode active material, the first negative electrode active material and the second negative electrode active material are each independently at least one of graphite, hard carbon, soft carbon, silicon-based material, titanium-based material, nitride, tinide, metallic lithium, silicon-doped graphite, and lithium titanate; preferably, the first negative electrode active material and the second negative electrode active material are the same material.
[0079] In some embodiments, the thickness of the polymer layer is less than or equal to the thickness of the first negative electrode active layer; and / or, the thickness of the polymer layer is the same as the thickness of the second negative electrode active layer.
[0080] Specifically, the thickness of the polymer layer is set to be less than or equal to the thickness of the first negative electrode active layer, which can not only ensure the performance of the negative electrode sheet, but also when the negative electrode sheet is placed in the electrolyte, the groove formed between two adjacent negative electrode active bosses can improve the ionic conductivity and high-rate charging performance of the battery.
[0081] Furthermore, setting the thickness of the second negative electrode active layer to be the same as that of the polymer layer can ensure that the negative electrode slurry does not cover the polymer slurry, thereby facilitating the dissolution of the polymer layer in the electrolyte to improve the ionic conductivity and high-rate charging performance of the battery.
[0082] The present invention further provides a method for preparing the negative electrode sheet as described above, the method comprising:
[0083] Step S100, coating a first negative electrode slurry on at least one surface of a current collector to obtain a first negative electrode active layer;
[0084] Step S200, coating a second negative electrode slurry and a polymer slurry on a surface of the first negative electrode active layer facing away from the current collector to form a composite layer to obtain the negative electrode sheet;
[0085] In the composite layer, the negative electrode slurry and the polymer slurry are both obtained by multi-striped coating.
[0086] In some embodiments, the step of coating the second negative electrode slurry and the polymer slurry on the surface of the first negative electrode active layer facing away from the current collector to form a composite layer comprises:
[0087] Coating the polymer slurry on the surface of the first negative electrode active layer facing away from the current collector in a multi-striped coating manner and performing a second drying process to form a polymer layer;
[0088] Applying a second negative electrode slurry in the gaps of the pre-coat layer to fill the gaps and performing a third drying process to obtain the composite layer;
[0089] or,
[0090] Coating a second negative electrode slurry on the surface of the first negative electrode active layer facing away from the current collector by a multi-striped coating method and performing a third drying process to obtain a second negative electrode active layer;
[0091] Applying the polymer slurry to fill the gaps in the second negative electrode active layer and performing a second drying process to obtain the composite layer;
[0092] or,
[0093] The polymer slurry and the second negative electrode slurry are simultaneously subjected to multi-stripe coating by using a double die head and then subjected to a fourth drying process to obtain the composite layer.
[0094] In some embodiments, after coating the first negative electrode slurry on at least one surface of the current collector and before obtaining the first negative electrode active layer, the preparation method further includes: performing a first drying treatment on the current collector coated with the negative electrode slurry.
[0095] Wherein, the first drying treatment is selected from one of a first drying treatment and an ultraviolet light curing treatment; and / or, the second drying treatment, the third drying treatment and the fourth drying treatment are independently selected from one of a second drying treatment and an ultraviolet light curing treatment.
[0096] In this embodiment, the slurry can be solidified faster through drying treatment, thereby improving the preparation efficiency of the electrode; preferably, the drying treatment is used in the first drying treatment and the third drying treatment, and the ultraviolet light curing treatment is used in the second drying treatment and the fourth drying treatment, because the polymer slurry is easier to shape using ultraviolet light, and the time required for the active layer to be cured by ultraviolet light is longer than that by drying treatment, which will result in energy waste and consumption.
[0097] The coating of the composite layer in the present invention includes three schemes, namely: first coating the polymer slurry and then coating the second negative electrode slurry, or first coating the second negative electrode slurry and then coating the polymer slurry, or coating the polymer slurry and the second negative electrode slurry at the same time; among them, the scheme of first coating the polymer slurry, curing it by ultraviolet light, and then coating the second negative electrode slurry and drying it has the best effect; because under such operation, the integrity of the polymer layer formed by the polymer slurry can be guaranteed as much as possible, and the possibility of the second negative electrode slurry and the polymer slurry flowing with each other during coating and causing the interface between the two to be blurred is greatly reduced; after each coating of the polymer slurry or the negative electrode slurry, an ultraviolet light curing or drying step must be performed to avoid the mixing of the negative electrode slurry and the polymer slurry during subsequent coating.
[0098] In this embodiment, the temperature of the first drying process is 40°C to 50°C;
[0099] And / or, the temperature of the second drying treatment is 55°C to 65°C;
[0100] And / or, the conditions of the UV curing treatment include: UV light intensity of 900W / cm 2 ~1100mW / cm 2 , the curing processing power is 30% to 50%, and the curing processing time is 5s to 15s.
[0101] In some embodiments, the first negative electrode slurry includes a first negative electrode active material, a binder, a thickener, and a first solvent; and / or, the polymer slurry includes a polymer and a second solvent; and / or, the second negative electrode slurry includes a second negative electrode active material, a binder, a thickener, and a first solvent.
[0102] In some embodiments, the concentration of the polymer slurry is greater than or equal to 10 mg / mL and less than or equal to 50 mg / mL;
[0103] And / or, the second solvent is deionized water.
[0104] In some embodiments, the first negative electrode active material and the second negative electrode active material are each independently at least one of graphite, hard carbon, soft carbon, silicon-based material, titanium-based material, nitride, tinide, metallic lithium, silicon-doped graphite, and lithium titanate; the binder is selected from at least one of polyvinylidene fluoride, carboxymethyl cellulose, polyvinyl alcohol, and sodium alginate; the thickener is selected from at least one of sodium carboxymethyl cellulose, hydroxypropyl methylcellulose, and guar gum; the first solvent is selected from at least one of deionized water, N-methylpyrrolidone, dimethylformamide and dimethylacetamide; and / or, the mass ratio of the first negative electrode active material, the binder and the thickener is (96-98):(1-2):(1-2); and / or, the mass ratio of the second negative electrode active material, the binder and the thickener is (96-98):(1-2):(1-2).
[0105] The present invention further provides a lithium-ion battery, which includes a shell, and a battery cell and an electrolyte disposed in the shell; the battery cell includes a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet;
[0106] Wherein, the negative electrode sheet is the negative electrode sheet as described above or the negative electrode sheet prepared by the method as described above.
[0107] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.
[0108] Example 1
[0109] A method for preparing a negative electrode sheet, comprising:
[0110] Step S1, graphite, CMC, and a binder are mixed uniformly in a mass ratio of 97.7:1.1:1.2 to prepare a lithium-ion battery negative electrode slurry having a certain viscosity;
[0111] Step S2, coating a layer of negative electrode slurry on the surface of the copper foil, and drying in an oven at 45° C. to form a first negative electrode active layer, the thickness of which accounts for half of the thickness of the entire negative electrode material;
[0112] Step S3, dissolving PU with a molecular weight of 10000 in deionized water to prepare 20 mg / mL PU slurry;
[0113] Step S4: Then, the surface of the electrode dried in step S2 is coated with a cross-sectional area of 0.02 mm at an equal interval of 1.5 mm. 2 PU slurry, at a strength of 1000mW / cm 2curing the film under ultraviolet light at 40% curing power for 10 seconds to form a polymer layer including a plurality of polymer bosses;
[0114] Step S5, coating the negative electrode slurry again between the polymer bosses obtained in step S4, the thickness of the PU slurry coating is the same as the thickness of the negative electrode slurry during the second coating, and the coated negative electrode slurry does not cover the polymer;
[0115] Step S6, drying at 60°C, cold pressing, and cutting into strips for later use.
[0116] Preparation of positive electrode:
[0117] Lithium iron phosphate, conductive agent superconducting carbon (Super-P), and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 97:1.5:1.5 to prepare a lithium-ion battery positive electrode slurry with a certain viscosity. The slurry is coated on a current collector aluminum foil, dried at 85°C, cold pressed, and cut into strips for later use.
[0118] Diaphragm: PE base film is coated with aluminum oxide / PVDF slurry on both sides, dried, and cut into strips for later use.
[0119] Electrolyte: Lithium hexafluorophosphate (LiPF6) was dissolved in a mixed solvent consisting of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) (the mass ratio of EC, DMC and EMC was 1:2:1) to obtain an electrolyte with a concentration of 1 mol / L.
[0120] Preparation of lithium-ion batteries:
[0121] The positive electrode sheet, separator, negative electrode sheet and electrolyte are rolled into a soft-pack battery, and left to stand at room temperature for 24 hours or at high temperature for 16 hours before use.
[0122] Example 2
[0123] This embodiment prepares a negative electrode sheet, which is different from the embodiment 1 in that:
[0124] The PU slurry was applied at equal intervals of 0.5 mm.
[0125] Example 3
[0126] This embodiment prepares a negative electrode sheet, which is different from the embodiment 1 in that:
[0127] The PU slurry was applied at equal intervals of 3 mm.
[0128] Example 4
[0129] This embodiment prepares a negative electrode sheet, which is different from the embodiment 1 in that:
[0130] The cross-sectional area of a single groove is 0.01 mm 2 PU slurry.
[0131] Example 5
[0132] This embodiment prepares a negative electrode sheet, which is different from the embodiment 1 in that:
[0133] The cross-sectional area of a single groove is 0.06 mm 2 PU slurry.
[0134] Example 6
[0135] This embodiment prepares a negative electrode sheet, which is different from the embodiment 1 in that:
[0136] The molecular weight of the coated polymer PU is 5000.
[0137] Example 7
[0138] This embodiment prepares a negative electrode sheet, which is different from the embodiment 1 in that:
[0139] The molecular weight of the coated polymer PU is 15,000.
[0140] Example 8
[0141] This embodiment prepares a negative electrode sheet, which is different from the embodiment 1 in that:
[0142] The coated polymeric PU was replaced by PEO.
[0143] Comparative Example 1
[0144] This example prepares a negative electrode sheet, which is different from Example 1 in that:
[0145] The negative electrode slurry was applied twice, and the PU slurry was not applied.
[0146] Comparative Example 2
[0147] This example prepares a negative electrode sheet, which is different from Example 1 in that:
[0148] The negative electrode sheet is laser etched to form grooves with a width of 1 mm and a spacing of 1.5 mm.
[0149] Comparative Example 3
[0150] This example prepares a negative electrode sheet, which is different from Example 1 in that:
[0151] Use equal mass of PU and negative electrode material, mix them evenly, and then coat them on the negative electrode foil.
[0152] Comparative Example 4
[0153] This example prepares a negative electrode sheet, which is different from Example 1 in that:
[0154] The PU slurry was applied at an equal interval of 0.2 mm.
[0155] Comparative Example 5
[0156] This example prepares a negative electrode sheet, which is different from Example 1 in that:
[0157] The PU slurry was applied at equal intervals of 5 mm.
[0158] Comparative Example 6
[0159] This comparative example prepares a negative electrode sheet, which is different from Example 1 in that:
[0160] The cross-sectional area of a single groove is 0.002mm 2 PU slurry.
[0161] Comparative Example 7
[0162] This comparative example prepares a negative electrode sheet, which is different from Example 1 in that:
[0163] The cross-sectional area of a single groove is 0.2 mm 2 PU slurry.
[0164] Comparative Example 8
[0165] This comparative example prepares a negative electrode sheet, which is different from Example 1 in that:
[0166] The molecular weight of the coated polymer PU is 1000.
[0167] Comparative Example 9
[0168] This comparative example prepares a negative electrode sheet, which is different from Example 1 in that:
[0169] The molecular weight of the coated polymer PU is 100,000.
[0170] Comparative Example 10
[0171] This comparative example prepares a negative electrode sheet, which is different from Example 1 in that:
[0172] The molecular weight of the coated polymer PU is 10000 and the cross-sectional area S is 0.08mm 2 .
[0173] Cycle and rate testing:
[0174] In the voltage range of 2.5V ~ 4.2V, the battery test system of Newwell Electronics Co., Ltd. was used to perform charge and discharge tests at rates of 0.2C, 0.5C, 1C, 3C, and 5C, respectively. The battery was charged and discharged 600 times at a constant current density of 3C. The test results are shown in Tables 1 and 2.
[0175] Liquid retention coefficient = liquid retention volume / battery capacity*1000
[0176] Performance test data:
[0177] Table 1: Specific capacity at 3C rate for 600 cycles
[0178]
[0179]
[0180] Table 2: Cycle specific capacity at different rates
[0181] sample 0.2C 0.5C 1C 3C 5C Example 1 168.1 152.4 134.7 121.4 107.9 Comparative Example 1 155.7 142.2 123.6 101.4 83.2 Comparative Example 2 163.7 149.6 129.4 112.3 93.2
[0182] Combined with the test results in Table 1, it can be seen from the data of Example 1 and Comparative Example 1 that after 600 cycles at a 3C rate, the discharge specific capacity of the battery in Example 1 is 109.3 mAh / g, which is 38.4 mAh / g higher than that of the battery in Comparative Example 1, and the liquid retention range difference in Example 1 is 0.2 smaller than that in Comparative Example 1, which shows that the grooves formed after the PU is dissolved by the electrolyte have good liquid retention consistency.
[0183] It can be seen from Example 1, Examples 4-7 and Comparative Examples 6-10 in Table 1 that the liquid retention consistency is also related to the cross-sectional area S of the groove and the molecular weight of the polymer PU.
[0184] It can be seen from Table 1 that when the groove cross-sectional area S ≥ 0.02 mm 2 As S increases, its liquid retention capacity increases, but its liquid retention consistency decreases. This is mainly because the larger the cross-sectional area of the PU-coated groove, the more space there is in the groove to accommodate the stored electrode liquid. However, the ability of the electrolyte to dissolve PU will weaken with the increase of PU, resulting in a decrease in its liquid retention consistency.
[0185] It can be seen from Example 1, Example 4 and Comparative Example 6 that when the groove cross-sectional area S is less than 0.02 mm 2 When S decreases, the space for the electrode to accommodate and store the electrolyte will be reduced, thus affecting its liquid retention capacity and consistency. The reduction in liquid retention consistency is mainly due to the reduction in PU and the reduction in its interaction with the electrolyte.
[0186] It can be seen from Example 1, Example 6 and Comparative Example 8 that when the PU molecular weight is less than 10000, as M decreases, the battery's liquid retention capacity is equivalent, but its liquid retention consistency decreases. This is mainly because the decrease in molecular weight affects the solvation reaction between the polymer and the salt in the electrolyte.
[0187] It can be seen from Example 1, Example 7 and Comparative Example 9 that when the PU molecular weight is ≥10000, as M increases, the liquid retention capacity and liquid retention consistency of the battery both show a downward trend. This is mainly because the increase in PU molecular weight increases the difficulty of electrolyte dissolution, resulting in incomplete dissolution of the polymer in the groove, affecting the battery's liquid retention capacity and liquid retention consistency, thereby affecting the battery performance.
[0188] It can be seen from Example 1 and Comparative Example 3 that the same mass of PU and negative electrode materials are mixed and coated, dissolved in the electrolyte to construct irregular ion channels, which shortens the Li + The migration path of the battery is not significantly improved to increase the rate charging effect. The battery discharge specific capacity after 600 cycles at a 3C rate is 16.9 mAh / g lower than that of Example 1. Compared with Comparative Example 3, the grooves formed in Example 1 are orderly shortened ion migration paths, and lithium ions are easier to pass through. However, Comparative Example 3 is simply mixed, and the disordered lithium ions are more difficult to pass through.
[0189] It can be seen from Examples 1 to 3 and Comparative Examples 4-5 that when the PU coating spacing is too narrow, it will cause certain challenges to the polymer coating process, and it is easy to cause the two polymer slurries to overlap, resulting in reduced liquid retention consistency and reduced battery performance. When it is too wide, the constructed ion channels are insufficient, which also leads to reduced cycle performance. The spacing of the polymer coating slurry is too wide or too narrow, which will lead to Li + The diffusion resistance increases, which is not conducive to Li + It can be seen from Examples 1 to 3 that when the coating spacing of PU is too narrow or too wide, it will lead to poor liquid retention consistency and decreased cycle performance.
[0190] It can be seen from Example 1 and Example 8 that when the polymer is replaced by PEO from PU, the initial discharge specific capacity at 3C rate differs by 9 mAh / g, and the discharge specific capacity after 600 cycles differs by ~13.7 mAh. This is mainly because polyurethane is more soluble in the electrolyte than PEO, and the groups in the polyurethane interact with the electrolyte.
[0191] K value test: put the battery at 45℃ / 24h, then test the first voltage U after standing at room temperature for 48h 1 Then let it stand at room temperature for 48 hours and test the voltage U for the second time 2 , according to the voltage drop twice, calculate K = (U 2 -U 1) / T, the test results are shown in Table 3.
[0192] Table 3: K value defective rate of batteries in different embodiments and comparative examples
[0193]
[0194]
[0195] It can be seen from Example 1 and Comparative Example 2 in Table 3 that the battery of Comparative Example 2 has a groove constructed by physical means such as laser etching, and the generated graphite debris cannot be effectively removed, which will cause self-discharge inside the battery. Its test K value mean is 0.0478mv / h, and the defect rate is 9.87%. The groove constructed by polymer dissolution does not have this problem. Its test K value mean is only 0.0341mv / h, and the defect rate is controlled at <0.1%. This solution can greatly enhance the safety of the battery compared to the traditional method.
[0196] Finally, the battery impedances of Examples 1 to 7 and Comparative Examples 1 to 10 were tested, and the test results are shown in Table 4.
[0197] Impedance test method: the open circuit voltage of the battery cell is U 1 , connect the positive and negative ears of the battery cell in parallel with an internal resistor R, force a large stable DC current to pass through it in a short time (usually 2 to 3 seconds), and measure the voltage U at both ends of the battery cell during discharge. 2 , and calculate the internal resistance of the lithium battery at that time according to the formula r=(U 1 -U 2 ) / (U 2 / R).
[0198] Table 4: Impedance and liquid retention consistency of batteries in different embodiments and comparative examples
[0199]
[0200]
[0201] It can be seen from Example 1 and Comparative Example 1 in Table 4 that the battery impedance of Example 1 is 3.7 mΩ lower than that of Comparative Example 1, that is, the additional ion transmission channel constructed by the electrode of the present application in the electrolyte can effectively improve the ion transmission capacity at the negative electrode. From the impedance values of Example 1 and Example 6, it can be seen that because the molecular weight of the polymer PU is small, the combination effect of PU and the electrolyte is affected, resulting in a large impedance of the battery cell and reduced cycle performance. This is because polyurethane has a typical two-phase structure, and the molecular soft segment composed of polyether can be solvated with the salt in the electrolyte, promoting ion transmission, improving the electrolyte ion conductivity, and reducing the impedance of the battery, thereby improving the battery cycle performance and charging rate.
[0202] It can be seen from Example 1 and Examples 6-7 in Table 4 that Example 1 has a 4≤S / M*10 compared to Examples 4 and 7. 7 ≤67 is large, mainly because the electrolyte in Example 1 dissolves the polymer PU more thoroughly, while there is polymer residue in the groove of the electrode in Example 7, resulting in poor consistency of battery liquid retention.
[0203] It can be seen from Example 1 and Comparative Examples 6-10 in Table 1 and Table 4 that the S / M*10 of Comparative Examples 6-10 7 The value of is not within the required range of 4 to 67. This is because the groove cross-sectional area and the polymer molecular weight affect the battery's liquid retention consistency, and the corresponding battery performance also decreases.
[0204] The above description is only a partial or preferred embodiment of the present invention. Neither the text nor the drawings can limit the scope of protection of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the overall concept of the present invention, or direct / indirect application in other related technical fields are included in the scope of protection of the present invention.
Claims
1. A negative electrode sheet, characterized in that: include: current collector; A first negative electrode active layer, wherein the first negative electrode active layer is disposed on at least one surface of the current collector; A polymer layer, the polymer layer comprising a plurality of polymer bosses, the plurality of polymer bosses being arranged at intervals on a surface of the first negative electrode active layer facing away from the current collector, wherein the polymer bosses are made of a polymer that can be dissolved in an electrolyte; A second negative electrode active layer, the second negative electrode active layer comprising a plurality of negative electrode active bosses, the plurality of negative electrode active bosses being arranged at intervals on a surface of the first negative electrode active layer facing away from the current collector, and each of the negative electrode active bosses being arranged between two adjacent polymer bosses; Wherein, the polymer boss is used to dissolve in the electrolyte when the negative electrode sheet is placed in the electrolyte, so as to form a groove between two adjacent negative electrode active bosses.
2. The negative electrode sheet according to claim 1, characterized in that: The polymer is selected from at least one of waterborne polyurethane, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, and polyvinylidene fluoride; and / or, the molecular weight of the polymer is 3000 to 50000; And / or, the melting point of the polymer is 50°C to 80°C.
3. The negative electrode sheet according to claim 1, characterized in that: The distance between any two adjacent polymer bosses is the same; And / or, the cross-sectional area of each polymer boss is greater than or equal to 0.01 mm 2 And less than 0.1mm 2 .
4. The negative electrode sheet according to claim 1, characterized in that: The distance between two adjacent polymer bosses is greater than or equal to 0.5 mm and less than 3 mm.
5. The negative electrode sheet according to claim 1, characterized in that: The cross-sectional area of a single groove and the molecular weight of the polymer satisfy the relationship: 4≤S / M*10 7 ≤67; Wherein, S is the cross-sectional area of a single groove, and M is the molecular weight of the polymer.
6. The negative electrode sheet according to claim 1, characterized in that: The first negative electrode active layer includes a first negative electrode active material, the second negative electrode active layer includes a second negative electrode active material, and the first negative electrode active material and the second negative electrode active material are each independently at least one of graphite, hard carbon, soft carbon, silicon-based material, titanium-based material, nitride, tinide, metallic lithium, silicon-doped graphite, and lithium titanate.
7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: The thickness of the polymer layer is less than or equal to the thickness of the first negative electrode active layer; And / or, the thickness of the polymer layer is the same as the thickness of the second negative electrode active layer.
8. A method for preparing a negative electrode sheet according to any one of claims 1 to 7, characterized in that: include: Coating a first negative electrode slurry on at least one surface of the current collector to obtain a first negative electrode active layer; Coating a second negative electrode slurry and a polymer slurry on the surface of the first negative electrode active layer facing away from the current collector to form a composite layer to obtain the negative electrode sheet; In the composite layer, the negative electrode slurry and the polymer slurry are both obtained by multi-striped coating.
9. The preparation method according to claim 8, characterized in that: The step of coating the second negative electrode slurry and the polymer slurry on the surface of the first negative electrode active layer facing away from the current collector to form a composite layer comprises: Coating the polymer slurry on the surface of the first negative electrode active layer facing away from the current collector in a multi-striped coating manner and performing a second drying process to form a polymer layer; Applying a second negative electrode slurry in the gaps of the pre-coat layer to fill the gaps and performing a third drying process to obtain the composite layer; or, Coating a second negative electrode slurry on the surface of the first negative electrode active layer facing away from the current collector by a multi-striped coating method and performing a third drying process to obtain a second negative electrode active layer; Applying the polymer slurry to fill the gaps in the second negative electrode active layer and performing a second drying process to obtain the composite layer; or, The polymer slurry and the second negative electrode slurry are simultaneously subjected to multi-stripe coating by using a double die head and then subjected to a fourth drying process to obtain the composite layer.
10. The preparation method according to claim 9, characterized in that: After coating the first negative electrode slurry on at least one surface of the current collector and before obtaining the first negative electrode active layer, the preparation method further comprises: performing a first drying treatment on the current collector coated with the negative electrode slurry.
11. The preparation method according to claim 10, characterized in that: The first drying process is selected from one of a first baking process and an ultraviolet light curing process; And / or, the second drying process, the third drying process and the fourth drying process are independently selected from one of a second baking process and an ultraviolet light curing process.
12. The preparation method according to claim 11, characterized in that: The temperature of the first drying treatment is 40°C to 50°C; And / or, the temperature of the second drying treatment is 55°C to 65°C; And / or, the conditions of the UV curing treatment include: UV light intensity of 900W / cm 2 ~1100mW / cm 2 , the curing processing power is 30% to 50%, and the curing processing time is 5s to 15s.
13. The preparation method according to claim 8, characterized in that: The first negative electrode slurry includes a first negative electrode active material, a binder, a thickener, and a first solvent; and / or, the polymer slurry comprises a polymer and a second solvent; And / or, the second negative electrode slurry includes a second negative electrode active material, a binder, a thickener, and a first solvent.
14. The preparation method according to claim 13, characterized in that: The concentration of the polymer slurry is greater than or equal to 10 mg / mL and less than or equal to 50 mg / mL; And / or, the second solvent is deionized water.
15. The preparation method according to claim 13, characterized in that: The first negative electrode active material and the second negative electrode active material are each independently selected from at least one of graphite, hard carbon, soft carbon, silicon-based material, titanium-based material, nitride, tin compound, metallic lithium, silicon-doped graphite, and lithium titanate; the binder is selected from at least one of polyvinylidene fluoride, carboxymethyl cellulose, polyvinyl alcohol, and sodium alginate; the thickener is selected from at least one of sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, and guar gum; the first solvent is selected from at least one of deionized water, N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; and / or, the mass ratio of the first negative electrode active material, the binder and the thickener is (96-98): (1-2): (1-2); And / or, the mass ratio of the second negative electrode active material, the binder and the thickener is (96-98):(1-2):(1-2).
16. A lithium ion battery, characterized in that: The invention comprises a shell, and a battery cell and an electrolyte arranged in the shell; the battery cell comprises a positive electrode sheet, a negative electrode sheet, and a separator arranged between the positive electrode sheet and the negative electrode sheet; Wherein, the negative electrode sheet is the negative electrode sheet as described in any one of claims 1 to 7 or the negative electrode sheet prepared by the method as described in any one of claims 8 to 15.
Citation Information
Cited By
Secondary battery and electronic apparatus
EP4734165A3
